Diseases and traumas of Pleistocene megafauna: A perspective from Poland - Pawłowska, Kamilla; Chrószcz, Aleksander; Poradowski, Dominik; Kubiak-Nowak, Dominika; Borawski, Wojciech (Wiley, 2025)
Analysis of pathologies can shed light on the health, trauma, and disease states of animals in the past. This study aims to explore the health status of megafauna during the Pleistocene and Holocene in Poland and to elucidate the diseases afflicting them, in order to gain a broader picture of the physical condition of these animals. For this purpose, species that show pathological lesions were macroscopically studied and CT images were used for reconstruction. These results are supplemented with previously published data. Our results show cases of traumatic lesions, inflammatory diseases, arthropathies, diseases associated with the environment, dental anomalies and oral pathology, congenital anomalies and inherited disorders, and others. Lesions were found on the skeletal elements of woolly rhinoceroses, woolly mammoths, aurochs, bovids, giant deer, elks, and bears. The diversity of pathological cases and taxa demonstrated here is the first contribution to empirical pathological research in Polish paleozoology dealing with Quaternary records. Besides this, the research presented in this paper contributes to building a bridge between paleozoology and zooarcheology in support of what we call the “one pathology” concept.
To jest manuskrypt artykułu, który ukazał się w International Journal of Osteoarchaeology, 2025; 0:e3387. DOI: https://doi.org/10.1002/oa.3387.
Keywords: mammals; paleopathology; Pleistocene; Poland